Polar Ocean Mixing by Internal Tsunamis (POLOMINTS) - Michael Meredith; Katharine Hendry; E. Povl Abrahamsen; J. Alexander Brearley; Emma Young; David Munday; Hugh Venables; Anna Hogg; Benjamin Wallis; Katrien Van Landeghem; Filipa Carvalho; Andrew Yool; et al. (Research Ideas and Outcomes)
Mixing of the ocean around Antarctica is a key process that exerts influences over large scales and in multiple ways. By redistributing heat in the ocean, it exerts strong influences on the Antarctic Ice Sheet, with implications for sea level rise globally. Similarly, the redistribution of ocean heat affects the production of sea ice in winter and its melt in summer, with consequences for climate. Mixing also affects the distribution of nutrients in the ocean, with direct impacts on the marine ecosystem and biodiversity and with consequences for fisheries.It was long thought that mixing of the seas close to Antarctica was predominantly caused by winds, tides and the loss of heat from the ocean especially in winter. However, we recently discovered that when glaciers calve in Antarctica, they can trigger underwater tsunamis. These are large (multi-metre) waves that move rapidly away from the coastline and when they break, they cause sudden bursts of very intense mixing. Simple calculations indicated that the net impact of these underwater tsunamis could be as strong as winds, and much more important than tides, in driving mixing. It was also argued that they are likely to be relevant everywhere that glaciers calve into the sea, including Greenland and across the Arctic. As our ocean and atmosphere continue to heat up, it is very possible that glacier calving will become more frequent and intensify, increasing further the impact of underwater tsunamis on large-scale climate, the cryosphere and ecosystems.This is an exciting new avenue of scientific investigation and many key questions remain unanswered. We need to know how widespread and frequent the generation of underwater tsunamis is, how far they travel from the coastline before breaking, and how variable this is. We need to measure what impacts the extra mixing has on ocean temperature and nutrient concentrations, and to determine what this means for the cryosphere and ocean productivity. There is a pressing need to include the effects of underwater tsunamis in the computer models that are used for projecting future ocean climate and ecosystem conditions and to determine the feedbacks between climate change and the generation of more underwater tsunamis.To answer these questions, our project will deploy innovative techniques for measuring the ocean and ice in close proximity to a calving glacier, including robotic underwater vehicles and remotely-piloted aircraft, and cutting-edge deep-learning techniques applied to satellite data. We will use advanced computer simulations to fully understand the causal mechanisms responsible for the creation and spread of the underwater tsunamis and their impacts on ocean climate and marine productivity. We will make our developments in computer simulation available to the whole community of users, for widespread uptake and future use.This project will have significant benefits for academics seeking to predict the future of Antarctica and its impacts on the rest of the world, for Governments and intergovernmental agencies seeking to understand how best to respond to climate change, and for the curious general public wanting to learn more about the extremes of the planet and why they matter. The fieldwork will be especially photo- and video-genic and will lead to outstanding outreach and impact opportunities, and we will work with media agencies seeking to tell compelling stories about the extremes of the Earth.